Transient isothermal gas flows in a pipeline using semi-discrete finite difference method and finite volume method - Agutaya, Jonas Karl Christopher N.
Computational methods offer an advantage over experiment-based approaches in determining various parameters in industrial pipelines mainly because of the large scale of the system under consideration. The algorithms used in such methods are developed from basic fundamental equations that govern the flow of the fluid. In this study, the semi-discrete finite difference method, which was coupled with the Euler method (FDM-Euler) and the Runger-Kutta 4th method (FDM-RK), and the finite volume method (FVM) were used to predict the pressure profile for a transient isothermal one-dimensional flow of a compressible gas in a pipeline. The modeling involved the simultaneous solution of the continuity equation and the equation of motion, which are both partial differential equations. Because of the complexities in solving these two equations, some assumptions were made to eliminate some terms in the equation of motion. Some of the input parameters for the simulations were taken from literature. A stable solution was obtained and the generated profiles were consistent with published results. Comparing the numerical methods used, FDM-Euler required the least computation time, followed by FVM, and then FDM-RK. The largest deviation between the results of the three methods was 5.58%. The algorithms developed were coded in Scilab (an open source software) and Mathcad, and can also be written in any programming language.